If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2x + 3 = 4 + 6 Reorder the terms: 3 + 7x + -2x = 4 + 6 Combine like terms: 7x + -2x = 5x 3 + 5x = 4 + 6 Combine like terms: 4 + 6 = 10 3 + 5x = 10 Solving 3 + 5x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5x = 10 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 10 + -3 5x = 10 + -3 Combine like terms: 10 + -3 = 7 5x = 7 Divide each side by '5'. x = 1.4 Simplifying x = 1.4
| -4(m-5)+7= | | -42+19=11 | | 9k+2=3k+14 | | -8X-9Y=36 | | -7.6(3.9k-7.8)-8= | | -96=8(x-6) | | 12-41/6 | | 6p-4=10p | | 10y-8y^3= | | 15N-50=10 | | 12n^3+84n^2=0 | | 1000x=325/999 | | -8x+6=-x+4 | | 12_41/6 | | M/4=13/8 | | 1.77+9.1y=3.2y | | 100x=26/99 | | 8w-22=25 | | 2ln(x-4)=ln(x+2)+ln(x+9) | | -27=8x-9-2x | | 10x=4/9 | | 2(u-2)-6u= | | 6w-1-8w=-9 | | 30-3/5x=x= | | .3x+.4y=1 | | 40p^3-70p^2=0 | | -7(x+1)-3=-2(3x+6) | | 4p=4p | | -7(x+1)-3=-2(3a+6) | | 7p+12+p=16 | | 10m-m=9 | | 30-3/5x= |